2004
DOI: 10.1111/j.0030-1299.2004.12722.x
|View full text |Cite
|
Sign up to set email alerts
|

Within‐population spatial synchrony in mast seeding of North American oaks

Abstract: Mast seeding, the synchronous production of large crops of seeds, has been frequently documented in oak species. In this study we used several North American oak data-sets to quantify within-stand ( B10 km) synchrony in mast dynamics. Results indicated that intraspecific synchrony in seed production always exceeded interspecific synchrony and was essentially constant over distances ranging from 100 m to 10 km. Asynchrony between species was at least partially attributable to differences in the endogenous dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
98
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 53 publications
12
98
0
Order By: Relevance
“…Synchrony within a species and section (1-year vs. 2-year) and asynchrony among species is common in American mixed oak formations Abrahamson and Layne, 2003;Liebhold et al, 2004). This same pattern has been observed in Southern Spain in mixed oak forests and dehesas in seven year data sets.…”
Section: Acorn Productionsupporting
confidence: 66%
See 2 more Smart Citations
“…Synchrony within a species and section (1-year vs. 2-year) and asynchrony among species is common in American mixed oak formations Abrahamson and Layne, 2003;Liebhold et al, 2004). This same pattern has been observed in Southern Spain in mixed oak forests and dehesas in seven year data sets.…”
Section: Acorn Productionsupporting
confidence: 66%
“…Therefore, it might be thought that South and South West aspects would be more productive. This effect has been observed in some North American oaks sites, whereas other stands did not show differences among orientations (Liebhold et al, 2004).…”
Section: Other Factors Affecting Acorn Productionsupporting
confidence: 53%
See 1 more Smart Citation
“…At a spatial scale similar to that used in our study, Martín-Vicente et al (1998) found differences of acorn production between mixed stands of Q. ilex, Q. suber and Q. canariensis, but in this case acorn production Acorn production and damage in holm oak 109 Liebhold et al (2004) reported synchrony between trees over distances less than 10 km in different Quercus species. In other oak species a trend of acorn production to synchronize over large geographic areas has been established (Sork et al, 1993;Healy et al, 1999;Koening and Knops, 2000).…”
Section: Variation In Acorn Productionsupporting
confidence: 65%
“…The success of trees that undergo mast seeding is commonly explained by the predator satiation hypothesis, which includes the prediction of seedling establishment, animal pollination, animal dispersal and accessory costs (Liebhold et al 2004;Fenner & Thompson 2005). Rodents often cache the acorns below the ground surface (Vander Wall 1994).…”
Section: Introductionmentioning
confidence: 99%